College students' performance in an introductory atmospheric science course: associations with spatial ability. (July 2016) - Yoon, So Yoon; Min, Ki‐Hong
ABSTRACT: Introductory science courses for non‐majors, taught in large lecture settings (>100 students) at public universities in the United States, face tough problems in matching the interests of the students who range from first‐year undergraduates to students in the final year with majors as diverse as liberal arts and engineering. To investigate the learning of atmospheric science by college students from various backgrounds, this study attempted to explore how the dynamics of students' learning varied by spatial ability, as defined by skills tested in a mental rotation test, gender and major (science, technology, engineering and mathematics (STEM) vs. non‐STEM), because the literature provides evidence of the importance of spatial ability in student achievement in science courses. Statistically significant correlations existed between spatial ability, perceived ability to use weather and climate information, overall content knowledge of atmospheric science, and final course grades. Although there were no gender or academic major dependencies in the final course grades, STEM majors performed better in a content knowledge survey. However, non‐STEM majors showed greater improvement overall.